Analisis Fatwa Syekh al-‘Uṡaimīn Tentang Keabsahan Haji Orang yang Meninggalkan Salat: Analysis of Syekh al- Uṡaimīn's Fatwa on the Validity of the Hajj of People Who Forget Prayer - M. Kasim; Muhammad Rezky Fauzy; Muhammad Nur Sayyid (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to analyze the fatwa of Shaykh al-ʿUthaymīn regarding the validity of the Hajj for an individual who abandons prayer. The research employs a descriptive qualitative method with a normative juridical approach through library research. The findings reveal three key points: first, according to Shaykh al-ʿUthaymīn, deliberately abandoning prayer may invalidate the validity of the Hajj, as it is regarded as an act of disbelief; second, this fatwa is grounded in the Qur’anic evidences, the Hadith, and the views of the Salaf scholars, who position prayer as the pillar of the religion and implicitly consider it a prerequisite for the validity of other acts of worship, including the Hajj; third, the fatwa holds significant relevance in the contemporary era, particularly in fostering awareness among Muslims of the urgency of maintaining prayer prior to performing the Hajj. The implications of this study highlight the importance of a comprehensive understanding of the interrelationship between the performance of prayer and the validity of the Hajj, as emphasized in Shaykh al-ʿUthaymīn’s fatwa. The study further demonstrates that the pillars of Islam cannot be practiced partially; rather, they must be observed holistically and consistently. These findings may also serve as a reference in religious guidance and in the development of daʿwah curricula, with the aim of strengthening the Muslim community’s understanding of prayer as the pillar of religion that supports the performance of other acts of worship, including the Hajj.